A COMPREHENSIVE UPDATE ON INCIDENCE, PREVALENCE AND COMPLEX ETIOLOGY OF CENTRAL LINE–ASSOCIATED BLOODSTREAM INFECTION IN PEDIATRIC INTENSIVE CARE UNITS IN KING SAUD MEDICAL CITY - Abdulrahiem, Juhaina; Sultan, Asia; Alaklobi, Faisl; Amer, Hala; Alzoman, Hind (International Journal of Research -GRANTHAALAYAH, 2021)
Central Line Associated Bloodstream Infection (CLABSI) is a type of bloodstream infection that is caused by microorganisms after the insertion of central lines. Paediatric Intensive Care Units have been studied to conduct this research on CLABSI in children from 2 to 15 years old. Children have been divided in two age groups that are 2-5 and 5-15 years. The Royal Children’s Hospital, Melbourne has been chosen as a sample of this besides other five hospitals of Australia. A total of 350 patients are studied in the course of this research and 216 among them were inserted with central lines. Bloodstream infection has been identified in 49 patients from these 216 patients and CLABSI occurred in 75.51% of them that is 37 patients. Associated microorganisms and other underlying diseases are listed in this study to develop an idea about factors responsible for CLABSI.